Role of Aripiprazole in the Treatment of Cardiovascular Disease - Iftikhar, Hassah Batool; Ali, Hassam (Cardiology and Cardiovascular Medicine, 2018)
The known cause of cardiac conduction disturbances predicts the cardiovascular side effects inducing severe arrhythmia by the use of atypical antipsychotic i.e. Aripiprazole The efficacies in co-morbidities absolutely risk the warning detection of sudden death cause with major mental disorders interacting the mechanism in the predisposing malignancy factors. Therefore, we believe to improve dose-dependent inhibition coding the life-threatening ventricular tachycardia based on cardiac toxicity issue regulate the evaluation of testing drug criteria in clinical practice.